Efeitos da intervenção da enfermagem-relaxamento nos níveis de ansiedade e de depressão em gestantes de alto risco - Araújo, Wanda Scherrer (2013)
High-risk pregnancy is that in which the pregnant's and/or fetus' health has higher chance to experience complications than the average in pregnancies. The whole context of the risk pregnancy and treatment may causes stress, bringing signs and prognostics as: apathy, depression, discouragement, dismay, emotional hypersensibility, anger, anxiety and irritability, and require more specialized technics of hospital care. Objective: To evaluate the effects of nursing interventionsrelaxation on anxiety levels and depression symptoms in pregnant women at high risk hospitalized. Methodology: This was a randomized clinical trial. The sample consisted of 25 pregnant women in the control group and 25 pregnant women in the experimental group that were hospitalized at the Hospital Universitario Cassiano Antonio de Moraes, Vitória-ES, with diagnosis of high-risk pregnancy at any gestational age, hospitalized for more than 24 hours. The technic of relaxation proposed by Benson and adapted by Amorim was applied. For data collection we used interview with record form, Inventory State-Trait Anxiety (STAI), Depression Scale Puerperal Edinburgh (EPDS). Blood pressure, heart rate and respiratory rate in the experimental group were measured before and after the intervention of NursingRelaxation. For statistical treatment of the data were used the Statistical Package for Social Sciences - SPSS, version 20.0. Results: The statistical tests Mann-Whytney, Wilcoxon test and t-test, showed a significant decrease in levels of state anxiety in the experimental group (p=0.001), from medium to low anxiety, and significant decrease in the levels of depression in the experimental group (p=0.000) after relaxation practice. Conclusion: The nursing intervention-relaxation should be incorporated into daily practice nurse in the care of women in the pregnancy.